The effect of inflation targeting (it) policy on the inflation uncertainty and economic growth in selected African and European countries - Shelter Thelile Nene; Kehinde Damilola Ilesanmi; Mashapa Sekome (Economies, 2022)
The study assessed the effect of inflation targeting (IT) policy on inflation uncertainty and economic growth in African and European IT countries. This study contributes to the existing knowledge by analysing and comparing the African IT and European IT countries using two advanced approaches which include the Generalized Autoregressive Conditional Heteroscedasticity (GARCH) and Panel Vector Autoregressive (PVAR). To determine how the IT policy affects the inflation uncertainty in selected countries, time series techniques were employed. Panel data approaches were used to determine the effect of inflation targeting on economic growth in the selected countries. The results are as follows: (1) Inflation Targeting policy is insignificant in reducing inflation uncertainty in South Africa, and the effect of the policy in Ghana is inconclusive; (2) The IT policy has a significant impact in reducing inflation uncertainty in European countries (i.e., Poland and the Czech Republic); (3) Inflation targeting has a negative impact on economic growth in African Countries; (4) The policy has a positive impact on economic growth in European Countries; (5) In comparison to European countries, the strategy has a negligible impact on economic growth in Africa. Overall, the results suggest that European countries inflation targeting regimes are more credible in terms of reducing the level of inflation uncertainty and sustaining economic growth compared to African countries. In this respect, policymakers must ensure that they assess the economic condition of an individual country before implementing such a policy.
Keywords: 330; economic growth; EGARCH model; GARCH model; inflation rate; inflation uncertainty; PVAR model